2013
DOI: 10.1099/mic.0.064329-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Salmonella enterica serovar Typhi Fur regulator and small RNAs RfrA and RfrB in iron homeostasis and interaction with host cells

Abstract: Iron is an essential element but can be toxic at high concentrations. Therefore, its acquisition and storage require tight control. Salmonella encodes the global regulator Fur (ferric uptake regulator) and the small regulatory non-coding RNAs (sRNAs) RfrA and RfrB, homologues of RyhB. The role of these iron homeostasis regulators was investigated in Salmonella enterica serovar Typhi (S. Typhi). Strains containing either single or combined deletions of these regulators were obtained. The mutants were tested for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 38 publications
0
45
0
Order By: Relevance
“…They are involved in protection against oxidative stress, bactericidal antibiotic and acid resistance, and survival within epithelial cells and macrophages (7,61). RyhB-2 is also implicated in the regulation of motility in S. Typhimurium, and the highest expression of both sRNAs in S. Typhi was obtained during interaction with host cells, which correlates with their role in virulence (27,62).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…They are involved in protection against oxidative stress, bactericidal antibiotic and acid resistance, and survival within epithelial cells and macrophages (7,61). RyhB-2 is also implicated in the regulation of motility in S. Typhimurium, and the highest expression of both sRNAs in S. Typhi was obtained during interaction with host cells, which correlates with their role in virulence (27,62).…”
Section: Discussionmentioning
confidence: 91%
“…For CFT073, we demonstrated that the ⌬fur mutant was more sensitive to H 2 O 2 than the wild-type parental strain in iron-poor and iron-rich media. Similarly, for S. Typhi, it has been shown that the sRNAs RyhB-1 and RyhB-2 are responsible for sensitivity of the ⌬fur mutant to H 2 O 2 , as enzymes required in response to oxidative stress resistance, such as superoxide dismutases, are repressed by RyhB (5,27). However, for CFT073, the ⌬ryhB ⌬fur double mutant was more sensitive to H 2 O 2 than the ⌬fur mutant in iron-rich medium and iron-poor medium, suggesting that other, unknown mechanisms are involved in the oxidative stress response in this strain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations